Pelaksanaan Pendidikan Karakter dalam Pembelajaran Agama Islam bagi Anak Tunalaras - Naufal Hidayatullah; Difa Ul Husna; Oktavianti Nendra Utami; Mau’idi Hafida (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Character education is aimed at students from all levels of education, including children with special needs such as children with disabilities. Children with disabilities with behavioral, emotional, and social disorders display poor behavior both personally and socially. Islamic religious education that provides knowledge about religion, especially Islam, and can educate disabled children with the application of religious values. Children's behavior is strongly influenced by the environment. Islamic religious education is expected to be able to provide attention and knowledge to children with mental disorders to develop good morals by following the process of Islamic religious education. The method used in this writing is a literature search related to the topic of this discussion, looking for sources from books and scientific articles. The purpose of this writing is to help Islamic Religious Education (PAI) teachers act as educators in Islamic learning to deepen the understanding of disabled children, especially their understanding of morals and morals. And the material adapts to the background of tunaIaras children.